Covalently linked heterofullerene-porphyrin conjugates; new model systems for long-lived intramolecular charge separation - Hauke, Frank; Atalick, Stefan; Guldi, Dirk Michael; Hirsch, Andreas; Hauke, Frank (Tetrahedron, 2006)
Attaching tetraphenyl porphyrins, with peripheral acetyl or malonate groups, to CN leads to the first covalently linked heterofullerene-porphyrin conjugates that exhibit long-lived intramolecular charge separation. © 2005 Elsevier Ltd. All rights reserved.